Analisis Partisipasi Siswa dalam Mengikuti Kegiatan Ekstrakurikuler di SMP Darul Hidayah Bangkalan - Suwaibatul Aslamiyah (Insan Cendekia : Jurnal Pendidikan dan Kebudayaan, 2024)
Extracurricular activities play an important role in supporting students' personal development by fostering their interests, talents, creativity, and social skills beyond classroom learning. However, students' participation in extracurricular activities has gradually declined, creating challenges for schools in maintaining the continuity of these programs. This study aims to analyze the forms of student participation in extracurricular activities at SMP Darul Hidayah Bangkalan and to identify the factors influencing students' involvement. The research employed a qualitative approach using a case study method. Data were collected through observations and interviews involving teachers and students at SMP Darul Hidayah. The findings indicate that student participation in extracurricular activities has decreased over the past several years. The decline is influenced by limited student interest, the shortage of competent extracurricular coaches, and the lack of students' motivation to develop their talents. Nevertheless, teachers and the school continue to encourage student involvement by providing guidance and maintaining extracurricular programs despite various constraints. Therefore, collaboration between schools, teachers, parents, and students is essential to improve students' participation and optimize the implementation of extracurricular activities as a medium for character development and talent enhancement.